Product and furniture design : the manufacturing guides. - Thompson, Rob, ....-; Kim, Young-Yun, ....- (London : Thames and Hudson, 2011)
This book, part of a new series built on the authority of Rob Thompsons highly acclaimed Manufacturing Processes for Design Professionals, includes new content selected specifically for the needs of students who create product and furniture designs for mass production. With some 450 specially commissioned photographs and technical illustrations, it describes more than 30 manufacturing processes, from the traditional and established to cutting- edge technologies.